Comparison of LDL-C Reduction Using Different Evolocumab Doses and Intervals: Biological Insights and Treatment Implications. (September 2018) - Wasserman, Scott M.; Sabatine, Marc S.; Koren, Michael J.; Giugliano, Robert P.; Legg, Jason C.; Emery, Maurice G.; Doshi, Sameer; Liu, Thomas; Somaratne, Ransi; Gibbs, John P.
Background: The proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor evolocumab reduces low-density lipoprotein cholesterol (LDL-C) and the risk of cardiovascular events. Objectives: To compare LDL-C reduction using evolocumab 140 mg once every 2 weeks (Q2W) or 420 mg monthly (QM) versus lower doses (70 mg Q2W or 280 mg QM) or placebo. Methods: Patients received evolocumab 70 or 140 mg Q2W, 280 or 420 mg QM, or placebo Q2W or QM in two 12-week phase 2 studies: one with and one without statins. Changes from baseline in LDL-C were compared across Q2W doses and across QM doses. Results: The analysis included 741 patients. Mean (95% confidence interval [CI]) reduction in LDL-C across Q2W visits through week 12 was 63.0% (60.3% to 65.7%) for evolocumab 140 mg Q2W, compared to 41.3% (38.6% to 44.0%) for 70 mg Q2W and 1.9% (4.6% reduction to 0.8% increase) for placebo Q2W (each P < .001 vs 140 mg Q2W), and 62.7% (60.1% to 65.3%) for 420 mg QM, compared to 55.5% (52.9% to 58.0%) for 280 mg QM and 2.5% (5.1% reduction to 0.1% increase) for placebo QM (each P < .001 vs 420 mg QM). Similar results were observed at the mean of weeks 10 and 12. In a subgroup (n = 151) with weekly assessments from weeks 8 to 12, mean (95% CI) peak effect on LDL-C reduction was 72.8% (67.7% to 77.9%) for 140 mg Q2W and 69.0% (63.6% to 74.3%) for 420 mg QM. Trough effect at week 12 underestimated LDL-C reduction. Median peak–trough variability was 20.5%, 21.1%, 31.9%, and 35.1% for evolocumab 140 mg Q2W, 420 mg QM, 70 mg Q2W, and 280 mg QM, respectively. Conclusion: Evolocumab 140 mg Q2W and 420 mg QM yielded similar LDL-C reduction. These doses sustained maximal LDL-C reduction, resulting in greater stability in LDL-C reduction over the dosing interval compared to lower doses. These results support evolocumab doses of either 140 mg Q2W or 420 mg QM.